Epigenetic modulation of social cognition: exploring the impact of methylation in brain-derived neurotrophic factor and oxytocin receptor genes across sex - Hye Yoon Park; Suonaa Lee; Se Jun Koo; Zhenxu Li; Eunchong Seo; Eun Lee; Suk Kyoon An (Scientific Reports)
Abstract Social cognition, which ranges from recognizing social cues to intricate inferential reasoning, is influenced by environmental factors and epigenetic mechanisms. Notably, methylation variations in stress-related genes like brain-derived neurotrophic factor (BDNF) and the oxytocin receptor (OXTR) are linked to distinct social cognitive functions and exhibit sex-specific differences. This study investigates how these methylation differences affect social cognition across sexes, focusing on both perceptual and inferential cognitive levels. Social cognitive abilities were assessed using the Korean version of the Reading the Mind in the Eyes Test (K-RMET) and Brune’s story-based Theory of Mind tasks (ToM-PST). DNA methylation levels in BDNF and OXTR were analyzed for correlations with performance on these cognitive tasks in a cohort of male and female participants. A moderation model was applied to determine if sex moderates the relationship between social cognition and DNA methylation. No significant overall correlation was found between social cognition and DNA methylation across participants. However, sex-specific correlations were identified, including a negative impact of BDNF methylation on K-RMET scores in males, and a similar effect of OXTR methylation on ToM-PST scores in females. The findings underscore the complex relationship between epigenetic modifications and social cognition, revealing sex-specific effects and highlighting the importance of considering sex in epigenetic studies of social cognition. This research contributes to understanding how epigenetic factors, influenced by sex, shape social cognitive processes and supports the need for sex-specific therapeutic approaches.